Calcium and Magnesium Levels in Children with Febrile Seizures Admitted in a Tertiary Care Hospital - Abbasi, Atif Naseem; Farooq Ikram; Saeed Zaman; Syed Hassan Nawaz; Sammar Hussain; Hassnain Shahid (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the diagnostic accuracy of hypocalcaemia and hypomagnesaemia in paediatric patients suffering from febrile seizures. Study Design: Cross-sectional validation study. Place and Duration of Study: Department of Pediatrics, Pak-Emirates Military Hospital, Rawalpindi Pakistan, Jul 2021 to Feb 2022. Methodology: We included 87 patients between the ages of 1-6 years with ongoing febrile illness who had a history of febrile seizures. Those with a history of febrile seizures within the last month, suffered from organic brain disease or were on drugs that altered serum calcium and magnesium levels were excluded. Patients were tested for serum magnesium and calcium on admission and remained admitted throughout the febrile period for observation of the development of seizures. Results: The mean age ± standard deviation of our sample was 3.23±1.50 years, with 46(52.9%) males. The serum magnesium levels demonstrated that 46(52.9%) had hypomagnesaemia at a cut-off of 1.4 mEq/L, which had a sensitivity of 70.3%, a specificity of 55.0% and diagnostic accuracy of 59.8% in predicting the development of febrile seizures. Serum calcium levels at a cut-off of 8.8 mg/dL showed that 36(41.4%) had hypocalcaemia, which carried a sensitivity of 48.2%, a specificity of 61.7% and a diagnostic accuracy of 57.5%. Conclusion: Both serum magnesium and calcium levels had comparable diagnostic accuracy in predicting whether a patient with a history of febrile seizures would go on to develop febrile seizures during the current illness. However, the individual diagnostic accuracy for this prediction could have been higher.